Capacity Development Strategy for School Administrative Staff to Support Improving the Quality of Education - Wibowo, Agus Hari; Timan, Agus; Sobri, Ahmad Yusuf (Proceedings Series of Educational Studies, 2024)
The capacity of school administrative staff plays an important role in improving the quality of education. Low administrative staff capacity in educational institutions can have a significant impact on the quality of educational services and student learning outcomes. Administrative staff capacity that is not optimal can also cause economic losses. This can affect the overall performance of the organization, including the quality of educational services provided. This research aims to identify and develop effective strategies in increasing the capacity of school administrative staff, so that they can contribute directly to improving the quality of education at various levels. The research approach used is a qualitative approach with data collection through literature study. Data sources focus on secondary data sources. The analysis technique used is thematic analysis. The findings obtained are that the strategy for developing the capacity of school administrative staff includes continuous training and development, the formation of a Professional Learning Community (PLC), a leadership role in supervision and support, effective collaboration and cooperation, and an integrated capacity development model.